Lysozyme thermal stability in the presence of cyclodextrins at different pH values - Díaz-Salazar, A Jessica; Ondo, Daniel (Biophysical chemistry, 2025)
In the present study, the primary action of native cyclodextrins (CDs) on lysozyme protein as binding ligand and secondary as aggregation inhibitor were probed. Thermally induced denaturation using differential scanning calorimetry (DSC) was measured in the presence of native α-, β- and γ-CDs. The denaturation process in CD absence was reversible to 60-80 % at pH≤6 with maximum Tm at pH=4. Denaturation in the presence of native α-CD at pH from 2 to 10, at the least stable and partially reversible conditions in presence of β-CD and γ-CDs at single pH 2 only, was measured. The protein thermal stability decreases in the presence of CDs, with the most evident for β-CD, followed by α-CD and almost no effect for γ-CD. The reversibility in the presence of α-CD was similar to that in its absence. The best protection performance against heat-induced denaturation was found at pH 2 for β-CD. The heat capacity data for α-CD at acidic pH were fitted by the protein-ligand binding model in the whole temperature and ligand concentration ranges studied. The decrease in thermal stability for α-CD at all pH, β- and γ-CD at pH 2 were fitted linearly as a function of ligand concentration. The CD-to-lysozyme binding parameters obtained in this work and from the literature for other CDs are briefly discussed using the concept of cyclodextrin cavity size, charge distribution, solvent accessible surface area and amino acid hydrophobicity.
Keywords: cyklodextriny; kur domácí; Protein Denaturation; koncentrace vodíkových iontů; Muramidase; denaturace proteinů; Temperature; muramidasa; Cyclodextrin; Calorimetry, Differential Scanning; Cyclodextrins; Inclusion complex lysozyme binding model; Enzyme Stability; diferenciální skenovací kalorimetrie; Animals; Hydrogen-Ion Concentration; Differential scanning calorimetry; Chickens; stabilita enzymů; zvířata; teplota